Problem-Based Learning Assisted by Jellyfish Game Media to Improve Student Learning Activity in Natural and Social Sciences - Haswin Haswin; Sinta Satria Dewi Pendit; Sisriawan Lapasere; Abdul Rahman; Putriwanti (Journal of Innovation and Research in Primary Education, 2026)
Low student learning activity in elementary science education remains a persistent challenge, particularly within Indonesia's newly implemented Independent Curriculum. This study addressed this problem by integrating Problem-Based Learning (PBL) with Jellyfish game media to improve student learning activity in Natural and Social Sciences (IPAS).  A Classroom Action Research (CAR) design following Kemmis and McTaggart's cyclical model—comprising planning, acting, observing, and reflecting—was conducted across two cycles with 24 fourth-grade students at SD Inpres Tipo, Palu City. Data were collected through validated observation sheets (inter-rater κ = 0.82), tests, interviews, and documentation, and analyzed using quantitative scoring and Miles et al.'s qualitative framework. Mean learning activity scores increased progressively from 45.41 (low) in the pre-cycle to 64.06 (moderate) in Cycle I and 86.77 (very good) in Cycle II, representing a total gain of 41.36 points. The most pronounced gain was observed in group discussion involvement. These findings demonstrate that game-assisted PBL effectively transforms passive student behavior into active, collaborative engagement, consistent with constructivist theory and the ICAP framework. The Jellyfish game functioned as a structural scaffold that redistributed participatory roles within learning groups, a novel contribution to game-based learning literature.